2019
DOI: 10.1149/2.1271904jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Processing and Heat Treatment Route on the Microstructure of MoS2/Polyetheretherketone Coatings Obtained by Electrophoretic Deposition

Abstract: In this work, molybdenum disulfide nanosheets were electrophoretically co-deposited with PEEK 708 microparticles to fabricate composite coatings on Ti-6Al-4V titanium alloy substrates. Different dispersion media, pure ethanol and ethanol with the addition of cationic chitosan polyelectrolyte have been studied. The co-deposition mechanisms were indicated based on zeta potential measurements and investigation of the interaction between particles in the suspension using electron microscopy. The composite coatings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…These two methods can also occur simultaneously as electrosteric stabilization [48]. Based on our previous studies [32,49], a cationic chitosan polyelectrolyte was used. To determine the stability of suspensions, a zeta potential of Si 3 N 4 and PEEK 708 particles were examined in pure ethanol and in ethanol-based dispersion media containing the addition of 15, 25 and 50 vol % of chitosan polyelectrolyte.…”
Section: Elaboration Of Suspensions For Epdmentioning
confidence: 99%
“…These two methods can also occur simultaneously as electrosteric stabilization [48]. Based on our previous studies [32,49], a cationic chitosan polyelectrolyte was used. To determine the stability of suspensions, a zeta potential of Si 3 N 4 and PEEK 708 particles were examined in pure ethanol and in ethanol-based dispersion media containing the addition of 15, 25 and 50 vol % of chitosan polyelectrolyte.…”
Section: Elaboration Of Suspensions For Epdmentioning
confidence: 99%
“…Nanocomposite performance depends on different factors such as dispersion, matrix-filler interactions, and, in case of flake and fibre reinforcements, alignment [10]. In this respect, EPD is useful to develop specific microstructures from multicomponent suspensions [14]; for instance, in the study of PEEK/MoS 2 coatings by electrophoretic codeposition, MoS 2 was found to align preferentially, parallel to the coating surface [15]. Similar preferential alignment of graphene oxide (GO) nanosheets has been reported in the EPD process [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature exists on the EPD of different PEEK-based coatings. [35][36][37][38][39][40][41] These works and our previous experience [14,42] proved that EPD and post-EPD heat treatment is a suitable method to produce pure PEEK 708 and PEEK 708-based coatings on titanium alloy substrates for tribological applications. The previously obtained PEEK 708, [7] Si 3 N 4 /PEEK 708, [14] and Al 2 O 3 / PEEK 708 [16] coatings on the Ti-6Al-4V alloy, despite a significant improvement in wear resistance in cooperation with an Al 2 O 3 ball at RT, had a relatively high COF of 0.27, 0.26, and 0.25, respectively.…”
Section: Introductionmentioning
confidence: 99%